The Effects of Nano-Hydroxyapatite and Casein Phosphopeptide-Amorphous Calcium Phosphate in Preventing Loss of Minerals from Teeth after Exposure to an Acidic Beverage (An In vitro Study) - Al-Janabi, Shahad Z; Al-Dahan, Zeyneb A (Journal of Baghdad College of Dentistry, 2015)
Background: To evaluate the effect of antierosive agents (10% Nano-Hydroxyapatite (NHA), 10% Casein Phophopeptide-Amorphous Calcium Phosphate (CPP-ACP), and combination of 10% NHA and 10% CPP-ACP) on loss of minerals from enamel surface of permanent teeth treated with antierosive agents when exposed to an acidic beverage and investigate the morphological changes of treated enamel surface after demineralization with cola based beverage under Scanning Electron Microscope (SEM).Materials and Methods: Sixty maxillary first premolars were randomly divided into four groups, 15 teeth for each group. Group I treated with 10% NHA, Group II treated with 10% CPP-ACP, Group III treated with 10% NHA and 10% CPP-ACP, and Group IV did not treat with any remineralizing agents. The teeth were immersed in the remineralizing solutions (10% NHA, 10% CPP-ACP, and combination of 10% NHA and 10% CPP-ACP) for 4 minutes twice daily for 28 days and then stored in the artificial saliva. The samples were immersed for 40 minutes in 20 ml Pepsi cola (PH=2.5). Atomic Absorption Spectrophotometer (AAS) was used to record the calcium and phosphorus concentrationsin Pepsi cola before and after demineralization with cola based beverage. SEM also usedto examine the morphological changes occurs in enamel surface of each group after demineralization with cola based beverage.Results: Statistically, there is a highly significant increase in calcium concentration in Pepsi cola (mg/dl) after demineralization with cola based beverage. Group I showed the lowest changes in calcium concentration values among the three studied groups. Group II was the next, which also showed lower changes in calcium concentration values, then group III while the highest changes were recorded in group IV. There is a highly significant reduction in phosphorus concentration in Pepsi cola (mg/dl) after demineralization with cola based beverage. Group I showed the lowest changes in phosphorus concentration values among the three studied groups. Group II was the next, which also showed lower changes in phosphorus concentration values, then group III while the highest changes were recorded in group IV. Statistically, a highly significant difference was showed in calcium and phosphorus concentrations between the four studied groups after demineralization with cola based beverage. Group IV has a highly significant difference in comparison to group I, group II, and group III. Conclusions: Both the remineralizing agents (NHA and CPP-ACP) were found to be effective in inhibiting the demineralization caused by cola based beverage.The combination of NHA and CPP-ACP had no synergistic effect on remineralization.